THE IMPACT OF APPLYING TRAINING STRATEGIES IN ACHIEVING THE BEST JOB PERFORMANCE-AN EXPLORATORY STUDY OF THE OPINIONS OF WORKERS IN GOVERNMENT BANKS OPERATING IN THE BAGHDAD GOVERNORATE - Ahmed Abdulsalam Ahmed Alsalim (Scholars Digest Publishing, 2024)
This study aimed to identify the impact of the applying of training strategies in achieving job performance, Study was based on the analytical descriptive approach. The study society is composed of employees of Iraqi government banks, which numbered (7) banks, Where the study sample was taken from these banks by a simple random sampling method The inspection unit was 200 personnel (administrative staff). Study found a number of results the level of training is related to years of management experience, as well as not specifying the training needs of the trainee accurately Because of the indifference of the departments in the banks in question to training and what it will achieve in improving performance. And based on the results achieved by the study, a set of recommendations were presented, the most important of which is to work on making a comparison between the evaluation of the expected performance and the current performance achieved "after implementing the training" and knowing whether the results are negative or positive in order to determine the training needs and develop the necessary training plans with the help of A group of specialists in the financial and banking field.